The Role of Inflammation in the Development of Osteoarthritis: A Review Based on Recent Studies: A Literature Review - Winata, Lionesya Sukma; Wardhani, Fitria Kusuma (Journal of Diverse Medical Research: Medicosphere, 2025)
Osteoarthritis (OA) is a degenerative condition characterized by cartilage destruction, subchondral bone changes, and inflammation, which can impair the quality of life of sufferers. This review aims to analyze the role of inflammation in the development of OA. The method used included a literature search of international and national databases for articles published in the last five years. The results showed that risk factors, such as age, obesity and trauma, can trigger the inflammatory process by involving pro-inflammatory cytokines such as IL-1β and TNF-α. Interventions for OA include pharmacological therapies, such as NSAIDs and corticosteroids, as well as non-pharmacological approaches through lifestyle modification. This review concludes that OA management requires an integrated approach to address inflammation and symptoms. A deeper understanding of the mechanisms of inflammation may support the development of more effective and efficient treatment strategies. Keywords: Osteoarthritis, inflammation pro-inflammatory cytokines, pharmacologic therapy, lifestyle modification.